Stare Decisis, the Charter and the Rule of Law in the Supreme Court of Canada - David, Lawrence (LexisNexis Canada, a member of the LexisNexis Group, 2020)
"Comprehensive study of the Canadian Supreme Court's practice in the field of stare decisis."– Provided by publisher.